Modern Xinjiang - Li, Xinping ("Charming Xinjiang" series, 2014)
Modern Xinjiang unfolds the outstanding achievements of Xinjiang in terms of transportation, urbanization, agriculture, industry, public service and people's livelihood and shows the happy life of all ethnic groups under the leadership of the Party Central Committee and the joint efforts of all ethnic groups since the reform and opening up.